1993
DOI: 10.1248/bpb.16.43
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Novel Hexapeptides with Neurotensin Activity in Rats.

Abstract: A high-performance liquid chromatographic method to determine (Me)Arg-Lys-Pro-Trp-tert-Leu-Leu (NT-2) with neurotensin (NT) activity in rat plasma was developed and a pharmacokinetic study was performed in rats. Quantitative analysis with high reproducibility was achieved for NT-2 over the concentration range of 1.14-500 ng/ml. (Me)Arg-Lys-Pro-Trp-tert-Leu-Leu-OEt (NT-1) was rapidly hydrolyzed to NT-2 in rat plasma at 37 degrees C. This degradation of NT-1 was observed as a pseudo first-order reaction, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Most, if not all, of these CNS effects of NT can be mimicked by systemic dosing of metabolically stable analogs of NT, most notably NT-2 (Machida et al, 1993;Sarhan et al, 1997) and NT69L (Cusack et al, 2000;Tyler-McMahon et al, 2000). NT is also known for its pharmacological effects on certain peripheral functions, including effects on intestinal motor and secretory activity (Kitabgi and Freychet, 1978), as well as certain ef- fects on endocrine and neuroendocrine function (Brown and Miller, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most, if not all, of these CNS effects of NT can be mimicked by systemic dosing of metabolically stable analogs of NT, most notably NT-2 (Machida et al, 1993;Sarhan et al, 1997) and NT69L (Cusack et al, 2000;Tyler-McMahon et al, 2000). NT is also known for its pharmacological effects on certain peripheral functions, including effects on intestinal motor and secretory activity (Kitabgi and Freychet, 1978), as well as certain ef- fects on endocrine and neuroendocrine function (Brown and Miller, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Like i.c.v. NT, the peripheral administration of the metabolically stable, brain-penetrant NT analog NT-2 (Machida et al, 1993;Banks et al, 1995) to wild-type mice also caused hypothermia, hot-plate analgesia, and reduced rotarod performance in vivo, but again these effects were absent in the NTR1 knockout mice. These results substantiate the importance of NTR1 in these activities and confirm the utility of these brain-penetrant NT analogs in studying the CNS actions of NT (Pugsley et al, 1995;Sarhan et al, 1997;Tyler et al, 1999;Cusack et al, 2000;Tyler-McMahon et al, 2000).…”
Section: Ntr1 Knockout Mice 311mentioning
confidence: 99%
“…All culture media were from Invitrogen (Cergy Pontoise, France). NT, neuromedin N, JMV449 (Doulut et al, 1992), and EISAI-2 (Machida et al, 1993) were from Neosystem (Strasbourg, France). EISAI-1 (Machida et al, 1993) was a generous gift of Eisai Co., Ltd. (Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…NT, neuromedin N, JMV449 (Doulut et al, 1992), and EISAI-2 (Machida et al, 1993) were from Neosystem (Strasbourg, France). EISAI-1 (Machida et al, 1993) was a generous gift of Eisai Co., Ltd. (Tokyo, Japan). Primary structures of these agonists are presented in Table 1 Receptor Expression and Cell Cultures.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that the degradation of (Me)Arg-Lys-Pro-Trp-tertLeu-Leu-OEt (NT-1) and nikkomycin Z, which were hydrolyzed in the solution, were accelerated in rat plasma. [5][6][7][8] We therefore theorized that SPN degradation might also be accelerated in rat plasma. However, the stability of SPN in rat plasma has not been reported, and the blood, serum, and plasma samples in the pharmacokinetic studies were treated without considering the stability of SPN in the samples.…”
mentioning
confidence: 99%